Social Determinants of Health and Health Confidence: A Cross-Sectional Study - Laura Truman PhD; Patricia Calero MA; Caroline Etland PhD; Razel B. Milo PhD; Cynthia D. Connelly PhD (SAGE Open Nursing)
Introduction Research shows low health confidence predicts poor involvement in self-care and is associated with increased use of costly healthcare services. To improve overall health and reduce health inequities, the relevance and urgency of identifying the relationship between social determinants of health and health confidence are great. Objective This study explored relationships between social determinants of health and health confidence in adults at an urgent care center in southern California. Methods The descriptive cross-sectional study collected data via survey from 240 English- and Spanish-speaking adults (18–93 years) receiving care for any medical condition between 15 and 17 August 2022. Patients in need of immediate medical attention were excluded. The survey encompassed The PRAPARE screening instrument , sociodemographic questions, and a single health confidence question. Bivariate analysis identified significant differences in health confidence for a logistic regression model. Results Forty-seven percent ( n  = 107) of participants reported low confidence in managing their health and well-being. Low health confidence was observed in those with unmet needs ( χ 2  = 4.16, p  = .042), and varying levels of stress ( χ 2  = 13.76, p  = .008). Low health confidence was common in low-income ( t  = 2.23, p  = .028) and greater social risk groups ( χ 2  = 19.7, p  < .001). Participants in contact with friends or family 1 to 5 times per week (vs. >5 times) were more likely to report low health confidence; those with high levels of stress were more likely to report low health confidence (vs. no stress). Conclusion This study highlights the insidious prevalence of social determinants of health and the impact of social isolation and stress on health confidence, providing the basis for implementing standardized social determinants of health screening.